2017
DOI: 10.1002/adfm.201702243
|View full text |Cite
|
Sign up to set email alerts
|

A Magnetoresistance Induced by a Nonzero Berry Phase in GeTe/Sb2Te3 Chalcogenide Superlattices

Abstract: The chalcogenide alloy Ge-Sb-Te (GST) has not only been used in rewritable digital versatile discs, but also in nonvolatile electrical phase change memory as a key recording material. Although GST has been believed for a long time not to show magnetic properties unless doped with magnetic impurities, it has recently been reported that superlattices (SLs) with the structure [(GeTe) L (Sb 2 Te 3 ) M ] N (where L, M, and N are usually integers) have a large magnetoresistance at room temperature for particular com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…By opposite, the composition and thickness of the Sb‐Te sublattice layer can vary depending on the different group and devices. For example, Simpson et al, Takaura et al, Ohyanagi and Takaura, and Saito et al reported a series of GST‐SLs with 4 nm Sb 2 Te 3 sublayers, Tominaga et al reported some GST‐SLs with 1 nm Sb 2 Te 3 sublayer, Momand et al and Casarin et al reported some GST‐SLs with 3 nm Sb 2 Te 3 sublayers, Wang et al reported a GST‐SL with 6 nm Sb 2 Te 3 sublayers. Moreover, Kalikka et al and Noé et al fabricated a series of GST‐SLs with thickness‐varied Sb 2 Te 3 sublayers (varied from 1 to 8 nm).…”
Section: The Atomic Structure Of Gst‐slmentioning
confidence: 99%
See 1 more Smart Citation
“…By opposite, the composition and thickness of the Sb‐Te sublattice layer can vary depending on the different group and devices. For example, Simpson et al, Takaura et al, Ohyanagi and Takaura, and Saito et al reported a series of GST‐SLs with 4 nm Sb 2 Te 3 sublayers, Tominaga et al reported some GST‐SLs with 1 nm Sb 2 Te 3 sublayer, Momand et al and Casarin et al reported some GST‐SLs with 3 nm Sb 2 Te 3 sublayers, Wang et al reported a GST‐SL with 6 nm Sb 2 Te 3 sublayers. Moreover, Kalikka et al and Noé et al fabricated a series of GST‐SLs with thickness‐varied Sb 2 Te 3 sublayers (varied from 1 to 8 nm).…”
Section: The Atomic Structure Of Gst‐slmentioning
confidence: 99%
“…In addition, although the GeTe sublayer in GST‐SL was often regarded as [(GeTe) 2 ] in previous models (Figure ), its thickness in samples/devices have been described as 0.7, 0.8, 0.9, or 1 nm in literatures depending on the publications and groups. Perhaps, this is due to how the GeTe‐sublayer thickness was defined or due to difficulty in the thickness control during material growth of GST‐SL.…”
Section: The Atomic Structure Of Gst‐slmentioning
confidence: 99%
“…By contrast, in a PCM cell based on a GST alloy, a high RESET current is needed to melt the material prior to amorphization. iPCMs open numerous opportunities for multilevel storage, hybrid devices combining resistive and magnetic memories, logic gate devices, and also devices for THz pulse detection . Incorporation of SLs in iPCM devices by using ULSI microelectronics technology has been demonstrated for large density memory arrays…”
Section: Introductionmentioning
confidence: 99%
“…All these models assume the existence of GeTe layers surrounded by Sb 2 Te 3 QLs in the SL. Interpretation of the magnetoresistance effects observed in SLs also rely on the existence of (GeTe) 2 blocks in the so‐called ferroelectric state. Nevertheless, high‐angle annular dark‐field scanning transmission electron microscopy (HAADF‐STEM) images of a [GeTe (1 nm)/Sb 2 Te 3 (3 nm)] 15 SL deposited by MBE reveal that Ge atoms have diffused into the adjacent Sb 2 Te 3 layers, which results in the local formation of different Ge–Sb–Te blocks containing either seven atomic planes (Ge 1 Sb 2 Te 4 ), nine atomic planes (Ge 2 Sb 2 Te 5 ), eleven atomic planes (Ge 3 Sb 2 Te 6 ), or thirteen atomic planes (Ge 4 Sb 2 Te 7 ) separated by vdW gaps .…”
Section: Introductionmentioning
confidence: 99%
“…Note that the SL structure consists of a ferroelectric normal insulator, GeTe, and a topological insulator (TI), Sb 2 Te 3 , and for certain structures it was shown using ab initio calculations that the RESET phase becomes a Dirac semimetal, while the SET phase becomes a Weyl semimetal . As can be anticipated from the characteristics of a TI, the band gap closes to give rise to a Dirac cone for certain thickness combinations or applied stress of the GeTe and Sb 2 Te 3 layers …”
mentioning
confidence: 94%